Development of smart solar-powered LED street lighting system for a greener community - Valerio, Wenceslao M.; Galita, Warlito M. (2013)
The major objective of the study is to design and develop a smart solar-powered LED street lighting system for a greener community. The project is different from conventional street lighting systems not only in the sense that it uses solar energy, but more importantly, it is also a stand-alone device that provides for an efficient energy management program that ensures effective maintenance and reduced energy wastage due to malfunctioning lighting controls. In addition, it is much cheaper to fabricate and maintain as compared with its commercially available counterparts. One important feature of the project is that it automatically controls the brightness of the LED lamp depending on a particular time of day, especially in cases where full level illumination is not needed, thus reducing power consumption. It automatically activates and deactivates lighting depending on the hours whereby daylight is sensed, thus ensuring a continuous cycle of charging and discharging the storage battery for maximum efficiency. All of these functions are possible since the project uses a controller, allowing for variable settings of time activation as well as brightness level, depending on the preference of the end-users.
Keywords: LED lighting; Green community